Levans production by Gluconacetobacter diazotrophicus - Molinari, María Laura (2013)
Background: Growth of Gluconacetobacter diazotrophicus with glucose as carbon an energy source has been extensively studied. However, there are no reports in the literature describing growth of G. diazotrophicus in cultures containing sucrose as carbon source. The first step in sucrose pathway and production of levans was investigated. Biomass, levans, gluconic acid and keto gluconic acids production and levansucrase activity were determined in cultures with different sucrose concentration and nitrogen sources. Results: The biomass production was maximal in cultures containing 100 g x L-1 sucrose and inorganic nitrogen. Gluconic acid production was observed under all conditions tested, at levels up to 9 g x L-1 in cultures with sucrose excess and biological N2-fixation (BNF). Keto gluconic acids were detectable only in cultures with sucrose excess and supplemented with organic nitrogen sources. Levans production, although observed in all cultures, was maximal in batch culture with 100 g x L-1 of sucrose and BNF, concomitant with a significant expression of extracellular levansucrase. Conclusions: Ours results not only describe some unknown aspects of G. diazotrophicus physiology, but open up the possibility of developing a technology of levans production by this organism using culture media with sucrose (or some cheaper substitute, like molasses) and without the addition of any N-source because of its ability of fixing atmospheric N2.